1978
DOI: 10.1128/aac.13.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Comparative distribution of gentamicin, tobramycin, sisomicin, netilmicin, and amikacin in interstitial fluid in rabbits

Abstract: We compared the penetration of five aminoglycosides into interstitial fluid (IF). IF was obtained in rabbits from Silastic tissue cages. Intramuscular injections were made: 1.5 mg/kg per dose for gentamicin (G), tobramycin (T), sisomicin (S), and netilmicin (N) and 7.5 mg/kg per dose for amikacin (A). Serum levels and IF concentrations were studied for 12 h after a single injection. IF levels were also compared in a six-injection study (one injection every 8 h). Peak serum levels were significantly higher with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Serum elimination half life after intramuscular administration was 54.6 min-' and after intraarticular administration 63.1 _+ 11.6 min-' (mean _+ S.D.). These results are similar to those reported for tobramycin in rabbits in other studies (Carbon et al 1978) and indicate that tobramycin diffuses quite freely over the synovial membrane in the rabbit knee joint when injected intraarticularly.…”
Section: Resultssupporting
confidence: 91%
“…Serum elimination half life after intramuscular administration was 54.6 min-' and after intraarticular administration 63.1 _+ 11.6 min-' (mean _+ S.D.). These results are similar to those reported for tobramycin in rabbits in other studies (Carbon et al 1978) and indicate that tobramycin diffuses quite freely over the synovial membrane in the rabbit knee joint when injected intraarticularly.…”
Section: Resultssupporting
confidence: 91%
“…Capillary sampling has been used interchangeably with venous sampling for the determination of theophylline (Frazer et al, 1983), phenytoin (Umstead & McKernon, 1981), and various biochemical and haematological parameters (Blumenfield et al, 1977;Stuart et al, 1974). However, significant venous-arterial concentration differences have been identified with a number of other drugs (Chiou & Lam, 1982) (Schentag et al, 1978), studies in rabbits have demonstrated that tobramycin distributes slowly into interstitial fluid with peak concentrations attained 34 h after peak concentrations in serum (Gerding et al, 1976;Carbon et al, 1978). Similarly, in human studies, ascitic fluid concentrations have been noted to peak about 4 h after administration (Sampliner et al, 1984 samples, the very high correlations between capillary and venous, and capillary and arterial, concentrations strongly suggest that arterialvenous concentration differences are negligible for tobramycin.…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial fluid concentrations of aminoglycosides are reported to peak at about 4 h post dose, and range between 25 and 50% of the serum level (Gerding et al, 1976;Carbon et al, 1978). This delayed, and relatively lower aminoglycoside level observed in interstitial fluid, could result in a significant lowering of the observed tobramycin level in a blood sample obtained by a finger lancet puncture, compared to that observed in a sample obtained by venepuncture.…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, despite similar pharmacokinetics in serum, it is not clear that the areas under the concentration-time curves are similar in the vegetations themselves. Therefore, Carbon et al (2) showed that of the aminoglycosides injected in 1.5-mg/kg doses, gentamicin induced higher interstitial levels than did tobramycin. In this work, we did not determine the early concentrations of aminoglycosides after administration of the bolus in the vegetations themselves, and a possible difference (in terms of local concentrations between drugs) cannot be excluded.…”
Section: Methodsmentioning
confidence: 99%